Pneumothorax and Subcutaneous Emphysema Evaluation in Patients with COVID-19 in the Intensive Care Unit - Mehtap Pehlivanlar Küçük; Burcu Öksüz Güngör; Ahmet Oğuzhan Küçük; Olcay Ayçiçek; Atila Türkyılmaz; Funda Öztuna; Yılmaz Bülbül; Tevfik Özlü (Galenos Yayinevi, 2021)
Objective:Pneumothorax (PNX) and subcutaneous emphysema (SCE) have increased in importance as a frequently occurring complication. This study aimed to reveal the frequency, timing, and possible risk factors in patients with PNX and SCE who are followed up with coronavirus disease-2019 (COVID-19) diagnosis in our tertiary intensive care unit (ICU).Materials and Methods:All patients with confirmed COVID-19 who were followed up and treated in our unit between August 8, 2020, and February 20, 2021, in a 16-bed tertiary ICU and who developed PNX and SCE during their hospitalization were included.Results:PNX and SCE developed in 16 (9.6%) of 165 patients who were followed up in our ICU due to COVID-19. Of these 16 patients, 3 (18.8%) survived. The median age of patients was 66.5 years (interquartile range: 58.5-75.5). Diabetes mellitus was the most common comorbidity in patients with PNX and SCE. Additionally, 12 (75%) patients had a smoking history. Of 15 (93.8%) patients who developed PNX, 4 (25%) were bilateral, and SCE developed in 9 (56.3%) patients. Twelve (75%) patients with PNX and SCE were under invasive mechanical ventilation, 3 (18.8%) under spontaneous breathing, and 1 (6.2%) under non-invasive mechanical ventilation treatment. The number of oxygen support days until the time PNX and SCE developed was 9 (6.25-17) days in the whole group, the median time was 6 days in the survival group and 9 days in the non-survival group.Conclusion:In the COVID-19 pandemic, complications, such as PNX and SCE, are more frequently observed (9.5%) than in the general intensive care population and the later period of intensive care admission (median 9 days). Smoking is defined as a risk factor in most of these patients; however, increased PNX rates are thought to be related to both COVID-19 pneumonia and parenchymal damage due to cytokine storms.